Laparoscopic Sleeve Gastrectomy Versus Laparoscopic Roux-en-Y Gastric Bypass: A Systematic Review and Meta-analysis of Weight Loss, Comorbidities, and Biochemical Outcomes From Randomized Controlled Trials. Issue 1 (January 2021) - Lee, Yung; Doumouras, Aristithes G.; Yu, James; Aditya, Ishan; Gmora, Scott; Anvari, Mehran; Hong, Dennis
Abstract : Objective: The aim of this study was to compare weight loss, obesity-related comorbidities, and biochemical outcomes of LSG versus LRYGB through a meta-analysis of randomized controlled trials (RCTs). Summary of Background Data: LSG and LRYGB are the 2 most commonly performed bariatric surgeries for the treatment of obesity. The comparative outcomes of the 2 surgeries is a topic of ongoing debate and medium-term outcomes remain uncertain. Methods: A search for RCTs comparing LRYGB versus LSG was conducted. Pooled outcomes between 2 procedures were compared using pairwise random-effects meta-analysis at 1, 3, and 5-year follow-up time points. Grading of recommendations, assessment, development, and evaluation was used to assess certainty of evidence. Results: Thirty-three studies involving 2475 patients were included. LRYGB resulted in greater loss of body mass index compared to LSG at 1 year [mean difference −1.25 kg/m 2, 95% confidence interval (CI) −2.01 to −0.49, P = 0.001; moderate certainty of evidence] which persisted at 3 years, but there was insufficient evidence at 5 years. Resolution of dyslipidemia was higher for LRYGB than LSG at 1 year (risk ratio 0.58, 95% CI 0.46–0.73, P < 0.001; moderate certainty of evidence) and 5 years (risk ratio 0.68, 95%CI 0.46–0.99, P = 0.04; low certainty of evidence). There was no difference between LRYGB and LSG for remission of type 2 diabetes, hypertension, and hemoglobin A1c, fasting insulin, homeostatic model assessment of insulin resistance, high-density lipoprotein, and the rate of 30-day major and minor complications. Conclusions: There are insufficient data from RCTs to draw any conclusions regarding the long-term comparative effectiveness beyond 3 years between LRYGB and LSG. Abstract : Supplemental Digital Content is available in the text